New developments in Islamic economics - Asmak Ab. Rahman (Emerald Publishing Limited, 2018)
New Developments in Islamic Economics: Examples from Southeast Asia investigates the latest developments in a vibrantand fast-moving area of practical financial and economic study. Primarilyfocused on Malaysian contexts, while also presenting perspectives fromIndonesia and Thailand, this book examines the Asian nations leading the worldin the application of Islamic finance.Case studies analyse anddiscuss new and emerging issues in Islamic economics, including microtakaful,waqf, social finance and poverty alleviation from an Islamic perspective.
Includes index.
Keywords: Economics -- Islamic countries.; Economics -- Southeast Asia.; Economics -- Religious aspects -- Islam.; Business & Economics, Islamic Banking & Finance.; Economic theory & philosophy.; elektronické knihy; electronic books